Solid electrolytic capacitor and method for manufacturing same

By forming a carbon coating on the cathode surface of the solid electrolytic capacitor, the problems of low high frequency electrostatic capacitance and high ESR in the prior art are solved, and a solid electrolytic capacitor with high electrostatic capacitance, low ESR and high temperature durability are realized.

CN119764062APending Publication Date: 2025-04-04NIPPON CHEMI CON CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510070085.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-12-17
Filing Date
2020-12-15
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing solid electrolytic capacitors have lower electrostatic capacitance in high frequency regions (such as 10kHz), higher equivalent series resistance (ESR), and insufficient high-temperature durability.

Method used

A cathode with a titanium carbide film, a carbon vapor deposition film or a carbon coated film is used to form a carbon coating layer on the surface of the valve metal foil of the cathode to increase the cathode capacitance and suppress the growth of the oxidation film. The specific method includes coating a carbon slurry containing carbon particles on the surface of the cathode substrate and forming a carbon coating layer by pressing treatment.

Benefits of technology

The electrostatic capacitance of solid electrolytic capacitors at high frequencies is improved, the ESR is significantly reduced, and good durability is maintained under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764062A_ABST
    Figure CN119764062A_ABST
Patent Text Reader

Abstract

Provided is a solid electrolytic capacitor having high capacitance, low ESR, excellent high-frequency characteristics, and high high-temperature durability. This solid electrolytic capacitor is provided with: a cathode (10) that has a cathode base (11) that is formed from a valve metal and has pits (11a), an oxide layer (12) that is provided on the surface of the cathode base (11) and is formed from an oxide of the valve metal, and a carbon coating layer (13) that is provided on the surface of the oxide layer (12) and contains carbon particles; the cathode substrate (11) is provided with an entering part (13a) which enters the corrosion pit (11a) and a penetrating part (13b) which penetrates through the oxide layer (12) and is communicated with the cathode substrate (11); an anode having an anode base formed of a valve metal, and a dielectric layer provided on the surface of the anode base and formed of an oxide of the valve metal constituting the anode base; and a solid electrolyte layer that is provided between the carbon coating layer of the cathode and the dielectric layer of the anode and contains a conductive polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application. The application number of the parent application is: 202080087832.5, the application date is: 2020.12.15, and the name of the invention is: solid electrolytic capacitor and its manufacturing method. Technical Field

[0002] The present invention relates to a solid electrolytic capacitor having a solid electrolyte layer containing a conductive polymer and a method for producing the same. Background Art

[0003] As electronic devices become smaller and faster, capacitors used in power circuits and the like are increasingly required to have high electrostatic capacitance, low equivalent series resistance (hereinafter referred to as "ESR"), excellent high-frequency characteristics, and high high-temperature durability. Among electrolytic capacitors having an anode, an electrolyte, and a cathode (apparent cathode), solid electrolytic capacitors (hereinafter referred to as "solid electrolytic capacitors using conductive polymers as electrolytes" are capacitors suitable for responding to the above requirements, wherein the anode is provided with an oxide film as a dielectric on the surface of a substrate formed of a valve metal such as aluminum, tantalum, niobium, etc. and subjected to a surface expansion treatment, the electrolyte is in contact with the oxide film and acts as a true cathode, and the cathode is in contact with the electrolyte and is formed of a valve metal.

[0004] However, on the surface of the cathode formed of valve metal in a solid electrolytic capacitor, there is generally a natural oxide film even if no treatment is performed to set an oxide film. Therefore, the electrostatic capacitance (C) of a solid electrolytic capacitor is as shown in the following formula, which is the combined capacitance of the anode capacitance (Ca) and the cathode capacitance (Cc). Even if the anode capacitance is increased by etching, as long as the cathode has capacitance, the capacitance of the capacitor will be smaller than the anode capacitance.

[0005] [Mathematical formula 1]

[0006]

[0007] Therefore, in order to increase the cathode capacitance of the solid electrolytic capacitor, an etching process is performed on the valve metal foil of the cathode. However, if the etching is too large, the surface dissolution of the valve metal foil will be promoted at the same time, which will hinder the increase of the surface expansion rate, and it is easy to form an oxide film on the surface of the valve metal foil. Therefore, there is a limit in the increase of the cathode capacitance based on the etching process and the maintenance of the cathode capacitance. Therefore, a method is proposed to increase the cathode capacitance and inhibit the growth of the oxide film by forming a film of a conductive material that is not easy to form an oxide film on the surface of the valve metal foil of the cathode.

[0008] For example, Patent Document 1 (Japanese Patent Publication No. 2000-114109) discloses a solid electrolytic capacitor having a cathode foil obtained as follows, wherein a chemical oxide film is formed on the surface of a valve metal foil subjected to an etching process, and then a film formed of a metal nitride such as TiN, ZrN, TaN, etc., which is not easy to form an oxide film, is formed thereon by a vapor deposition method. According to the description, since a part of the chemical oxide film is removed by vapor deposition of the metal nitride and the metal nitride is connected to the valve metal foil, the cathode capacitance becomes infinite, and the capacitance (C) of the capacitor shown in the above formula is equal to the anode capacitance (Ca) and reaches the maximum. In addition, it is specifically shown that the capacitor of the embodiment using the cathode foil with a TiN film formed on the chemical oxide film has a high electrostatic capacitance and a low dielectric loss compared with the capacitor of the comparative example using the cathode foil with only a chemical oxide film formed thereon. In addition, Patent Document 2 (Japanese Patent Publication No. 2005-109272) discloses a solid electrolytic capacitor having a cathode foil obtained by forming a chemically-oxidized film on the surface of a valve metal foil subjected to etching, and then forming a film formed of a metal carbide with low specific resistance such as TiC, WC, or ZrC by vapor deposition. According to the description, due to the low specific resistance of the metal carbide, the conductive polymer and the cathode foil are in a conductive state, so that the combined capacitance of the capacitor reaches the maximum, and the adhesion between the metal carbide and the conductive polymer is good, so the ESR is reduced. In addition, it is specifically shown that the capacitor of the embodiment using the cathode foil having the TiC film has a high electrostatic capacitance and a low ESR compared with the capacitor of the comparative example using the cathode foil having the TiN film instead of the TiC film.

[0009] For the solid electrolytic capacitors disclosed in Patent Documents 1 and 2, the problem of the capacitor capacitance being reduced by the slow growth of an oxide film on the surface of the metal nitride or metal carbide of the cathode is pointed out. Therefore, in order to solve this problem, a method of using a carbon film instead of the film of the metal nitride or metal carbide is proposed. For example, Patent Document 3 (Japanese Patent Publication No. 2006-190878) discloses a solid electrolytic capacitor having a cathode with a carbon film formed on the surface of a valve metal using a dry plating method such as an ion plating method. According to the description, since the carbon film is fixed to the surface of the valve metal and no oxide film is formed on the valve metal, the cathode capacitance is basically asymptotic to infinity and the capacitor capacitance is only the anode capacitance. In addition, it is shown that if a cathode foil with a carbon film formed by ion plating is used on an aluminum foil subjected to etching, the electrostatic capacitance of the solid electrolytic capacitor at 120Hz becomes higher than the case where an aluminum foil without a carbon film is used as the cathode foil. In addition, there is also a known technique for forming a carbon film by coating. For example, Patent Document 4 (Japanese Patent Publication No. 2007-095865) discloses a method for manufacturing an aluminum cathode foil for an electrolytic capacitor in which a metal film such as Ti is formed on the surface of a roughened aluminum material and carbon particles are fixed on the upper side of the metal film. In the embodiment, a Ti film is formed on an aluminum foil subjected to an etching treatment by vacuum evaporation or sputtering, and then a coating material in which carbon particles are dispersed in an organic binder is applied and heated to form the cathode foil. In addition, as a comparative example, a cathode foil formed by directly coating the coating material on the aluminum foil subjected to an etching treatment and heating is also shown. In the embodiment and the comparative example, substantially the same electrostatic capacitance is obtained except for the capacitance change before and after the formation treatment in which the opposite voltage is assumed to be applied.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Application Publication No. 2000-114109

[0013] Patent Document 2: Japanese Patent Application Publication No. 2005-109272

[0014] Patent Document 3: Japanese Patent Application Publication No. 2006-190878

[0015] Patent Document 4: Japanese Patent Application Publication No. 2007-095865 Summary of the invention

[0016] Problems to be solved by the invention

[0017] Solid electrolytic capacitors have the advantages of being small, large in capacitance, and low in ESR, and are also easy to chip (Japanese: chipization). However, the evaluation of the electrostatic capacitance of capacitors so far is generally carried out under the condition of a frequency of 120Hz, and the evaluation in the high-frequency region is insufficient. Therefore, the inventors and others measured the electrostatic capacitance of the prior art solid electrolytic capacitors having a cathode with a titanium carbide film, a carbon vapor-deposited film, or a carbon-coated film at 10kHz, and found that any capacitor showed a lower capacitance, which should be improved. In addition, the ESR of the above-mentioned solid electrolytic capacitors was measured under the conditions of a frequency of 10kHz and 100kHz, and the result was that any capacitor showed a higher ESR value. On the other hand, as mentioned above, solid electrolytic capacitors are required to have high electrostatic capacitance, low ESR, excellent high-frequency characteristics, and high high-temperature durability.

[0018] Therefore, an object of the present invention is to provide a solid electrolytic capacitor that can meet the above-mentioned requirements.

[0019] Means for solving problems

[0020] In PCT / JP2019 / 022741, which was unpublished when the applicant filed the application that is considered as the basis for the priority claim of the present application, an electrode body used in the cathode of an electrolytic capacitor showing good capacitance was disclosed, characterized in that it has a cathode body formed of a valve-acting metal and having a surface expansion layer formed on the surface, and a carbon layer formed on the surface expansion layer, and the boundary between the surface expansion layer and the carbon layer has a concave-convex shape. In addition, as a method for manufacturing an electrode body with suitable performance, a method of applying a slurry containing carbon particles on the surface of the cathode body and applying a pressing treatment after drying was disclosed. If the method is implemented using an aluminum foil to which an etching treatment has been applied as a substrate, the carbon particles can be pressed into the etched pits of the aluminum foil by the pressing treatment, and the carbon particles can be made to pierce the oxide film on the aluminum foil, so that the carbon coating layer is conductive with the aluminum of the substrate.

[0021] In PCT / JP2019 / 022741, although the performance of the wet electrolytic capacitor using the above-mentioned electrode body as the cathode is described in detail, there is no record of the performance of the solid electrolytic capacitor using the above-mentioned electrode body as the cathode. The inventors used the above-mentioned electrode body with suitable performance as the cathode to make a solid electrolytic capacitor and evaluated the performance of the obtained capacitor. It was found that not only the capacitance at a frequency of 120Hz increased, but also the capacitance at a frequency of 10kHz increased, the ESR at a frequency of 10kHz and the ESR at 100kHz were significantly reduced, and after a charge and discharge test at a high temperature of 105°C as a durability test, it was confirmed that the electrostatic capacitance and ESR of the capacitor changed little, thereby achieving the present invention.

[0022] Therefore, the present invention firstly relates to a solid electrolytic capacitor, characterized by comprising:

[0023] A cathode having a cathode substrate, an oxide layer and a carbon coating layer, wherein the cathode substrate is formed of a valve metal and has an etch pit, the oxide layer is provided on the surface of the cathode substrate and is formed of an oxide of the valve metal, and the carbon coating layer is provided on the surface of the oxide layer and contains carbon particles, and has an entry portion that enters the etch pit and a penetration portion that penetrates the oxide layer and is in electrical communication with the cathode substrate;

[0024] An anode having an anode substrate formed of a valve metal and a dielectric layer formed of an oxide of the valve metal constituting the anode substrate and provided on a surface of the anode substrate;

[0025] The solid electrolyte layer is provided between the carbon coating layer of the cathode and the dielectric layer of the anode and contains a conductive polymer.

[0026] In addition, the present invention relates to a method for manufacturing a solid electrolytic capacitor, which is the above-mentioned method for manufacturing a solid electrolytic capacitor, characterized in that it includes:

[0027] The cathode forming step comprises: a coating stage, coating a carbon slurry containing carbon particles on the surface of an oxide layer formed of an oxide of the valve metal provided on the surface of a cathode substrate formed of the valve metal and having an etch pit, and drying the coating to form a slurry layer; and a pressing stage, applying a pressing treatment to the slurry layer to press the carbon particles into the etch pits and to make the carbon particles pierce the oxide layer, thereby forming a carbon coating layer having an entry portion that enters the etch pits and a penetration portion that penetrates the oxide layer and is in electrical communication with the cathode substrate;

[0028] an anode forming step of forming a dielectric layer by oxidizing a surface of an anode substrate formed of a valve metal; and

[0029] The electrolyte forming step forms a solid electrolyte layer including a conductive polymer between the carbon coating layer of the cathode and the dielectric layer of the anode.

[0030] The etch pits in the cathode substrate may be tunnel pits, sponge pits, through-type pits, or residual core pits, and the oxide layer provided on the surface of the cathode substrate may be a chemically formed oxide film or a natural oxide film. It should be noted that in this specification, the portion of the cathode other than the carbon coating layer is sometimes referred to as a "current collector".

[0031] During the pressing stage of the cathode forming process, if pressure is applied to the slurry layer, the carbon particles pierce the above-mentioned oxide layer and conduct with the cathode substrate to form a penetrating portion of the carbon coating layer, and the carbon particles are pressed into the above-mentioned etch pits to form an entry portion of the carbon coating layer. If the average value of the length of the entry portion of the carbon coating layer is greater than 1 / 5 of the average value of the length of the etch pit, and preferably greater than 1 / 4, the close adhesion between the carbon coating layer and the collector in contact with the carbon coating layer can be properly ensured to reduce the interface resistance between the carbon coating layer and the collector, and the peeling of the carbon coating layer can be properly suppressed. Here, the so-called "length of the etch pit" is equal to the thickness of the cathode substrate when the cathode substrate has a penetrating type etch pit, and refers to the length of the etch pit from the opening position to the bottom when the cathode substrate has a residual core type etch pit. Figure 1 In the example shown, the symbol Ha is added. In addition, the so-called "length of the entry portion of the carbon coating layer" refers to the length of the entry portion from the opening position of the etch pit to the position farthest from the opening position. Figure 1 In the example shown, the symbol Hb is added. The average value of these values ​​can be obtained by referring to a SEM photograph of a cross section of the cathode at a magnification of 5000 times and averaging the values ​​obtained for each etch pit and the intrusion portion.

[0032] The pressure in the pressing stage of the cathode forming step is preferably adjusted so that the interface resistance of the cathode is 10 mΩcm 2 Below, preferably 6 mΩcm 2 Below, more preferably 3mΩcm 2 In the pressing stage, the interface resistance is set to 10 mΩcm. 2In the following, the conduction between the carbon coating layer and the cathode substrate and the adhesion between the carbon coating layer and the current collector can be appropriately ensured. It should be noted that the so-called "interface resistance of the cathode" refers to the interface resistance measured between the carbon coating layer and the cathode substrate, which depends on all interfaces contained in the cathode, and can be obtained by a known measurement method, for example, it can be obtained by the following method. First, a cathode having a carbon coating layer with a thickness of 20 to 30 μm is formed. Then, an arrangement of a plurality of measuring test needles for measuring the potential of the surface of the carbon coating layer at many positions, and an arrangement of probes composed of applying test needles for applying current to the cathode arranged around the arrangement are brought into contact with the surface of the carbon coating layer, a prescribed DC current is applied between the applying test needles, and the potential generated on the surface of the carbon coating layer when the current is applied is measured at many positions using the measuring test needles, thereby obtaining the measured value of the potential distribution. Then, a model formula is constructed in which the measured thickness of the collector, the resistance of the collector, and the thickness of the carbon coating layer are set as fixed values, and the resistance of the carbon coating layer and the interface resistance are set as variables, and the potential distribution of the model formula is calculated while changing the variables. Thereafter, the interface resistance when the calculated value of the potential distribution obtained by the model formula is consistent with the measured value of the potential distribution is the "interface resistance of the cathode". As a device suitable for obtaining the interface resistance of the cathode, for example, the electrode resistance measurement system RM2610 manufactured by Hioki Electric Chemical Co., Ltd. can be cited. There is no particular limitation on the thickness of the carbon coating layer as long as the entire surface of the oxide layer and the cathode substrate to be covered by the carbon coating layer is covered, for example, it can be set to an average thickness of 0.5 to 30 μm. In the above-mentioned measurement method using the potential distribution, a carbon coating layer with a thickness of 20 to 30 μm is used, but the value of the interface resistance of the cathode obtained by pressing a thinner carbon coating layer with the same pressure is similar to the value of the interface resistance of the cathode having a carbon coating layer with a thickness of 20 to 30 μm.

[0033] Since the carbon coating layer of the solid electrolytic capacitor of the present invention has an entry portion that enters the etch pit of the cathode substrate, it naturally contains at least carbon particles with a particle size that can enter the above-mentioned etch pit. However, in a suitable embodiment of the present invention, the above-mentioned carbon coating layer also contains carbon particles with a particle size that cannot enter the above-mentioned etch pit. Therefore, the carbon slurry used in the coating stage of the cathode forming process also contains carbon particles with a particle size that cannot enter the above-mentioned etch pit. For this particle, even if only a part enters the etch pit, there will be no situation where all particles enter the etch pit, so it is substantially present in the area other than the entry portion in the carbon coating layer. However, in the pressing stage of the cathode forming process, the particle plays a role in compressing and deforming the etch pit to appropriately improve the adhesion between the carbon coating layer and the collector contacting the carbon coating layer, and appropriately reduce the interface resistance between the carbon coating layer and the collector. In addition, in the pressing stage of the cathode forming process, the particle plays a role in properly pressing the carbon particles with a particle size that can enter the etch pit into the etch pit. On the other hand, carbon particles having a particle size capable of entering the etch pits are not only filled into the entry portion of the carbon coating layer, but also filled into the gaps between large carbon particles that exist only in the area other than the entry portion, and exist in the entire carbon coating layer. It should be noted that the so-called "carbon particles" refer to particles that are identified as a structural element of a whole block in the carbon coating layer, and can be primary particles, secondary particles, or higher-order particles. The term "particle size" corresponds to the above-mentioned particle morphology and refers to the particle size of primary particles, the particle size of secondary particles, or the particle size of higher-order particles.

[0034] As carbon particles for forming the carbon coating layer, carbon particles having various shapes such as fibrous, spherical, and scaly can be used without particular limitation, and examples include porous carbon such as carbon nanotubes, carbon nanofibers, carbon nanohorns, activated carbon, carbon black such as Ketjen black, furnace black, channel black, and acetylene black, amorphous carbon, natural graphite, artificial graphite, graphitized Ketjen black, and mesoporous carbon. In the case where the carbon coating layer contains carbon particles having a particle size that cannot enter the etch pit, the carbon particles can be formed by the same type of carbon. In other words, the same type of carbon having a wide range of particle size distribution, such as acetylene black having a wide range of particle size distribution, can be used to form the carbon coating layer. In this case, the carbon particles having a particle size that cannot enter the etch pit among the same type of carbon play the above-mentioned role. In addition, a mixture of different types of carbon, such as a mixture of flaky graphite and acetylene black, can also be used to obtain a wide range of particle size distribution of carbon particles. Furthermore, if the carbon particles having a particle size that cannot enter the etch pits are formed of flaky graphite, the flaky graphites are easily oriented in such a way that the basal planes overlap each other, thereby compressing and deforming the etch pits, and easily piercing the oxide layer to conduct with the cathode substrate. In addition, if flaky graphite and carbon black are used together, the carbon black is easily pressed into the etch pits and between the flaky graphites, forming a carbon coating layer that is particularly dense and has excellent conductivity and excellent adhesion to the collector, and as a result, a solid electrolytic capacitor with particularly excellent high-frequency characteristics and high-temperature stability can be obtained.

[0035] Effects of the Invention

[0036] The solid electrolytic capacitor of the present invention exhibits high electrostatic capacitance, low ESR, excellent high-frequency characteristics, and high high-temperature durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a schematic diagram schematically showing an enlarged view of a region near the carbon coating layer of a cathode cross section.

[0038] Description of Reference Numerals

[0039] 10 cathode, 11 cathode substrate, 11a etch pit, 11b outer surface, 11c etch pit surface, 12 oxide layer, 13 carbon coating layer, 13a entry portion, 13b penetration portion, Ha the length of the etch pit, Hb the length of the entry portion. DETAILED DESCRIPTION

[0040] The solid electrolytic capacitor of the present invention comprises:

[0041] A cathode having a cathode substrate, an oxide layer and a carbon coating layer, wherein the cathode substrate is formed of a valve metal and has an etch pit, the oxide layer is provided on the surface of the cathode substrate and is formed of an oxide of the valve metal, and the carbon coating layer is provided on the surface of the oxide layer and contains carbon particles, and has an entry portion that enters the etch pit and a penetration portion that penetrates the oxide layer and is in electrical communication with the cathode substrate;

[0042] An anode having an anode substrate formed of a valve metal and a dielectric layer formed of an oxide of the valve metal constituting the anode substrate and provided on a surface of the anode substrate; and

[0043] The solid electrolyte layer is provided between the carbon coating layer of the cathode and the dielectric layer of the anode and contains a conductive polymer.

[0044] By utilizing the special carbon coating layer, a solid electrolytic capacitor having high electrostatic capacitance, low ESR, excellent high frequency characteristics, and high high temperature durability can be provided. The solid electrolytic capacitor can be manufactured by the method shown below, which includes a cathode forming step, an anode forming step, and an electrolyte forming step. Each step is described in detail below.

[0045] (1) Cathode formation process

[0046] The cathode forming process includes: a coating stage, coating a carbon slurry containing carbon particles on the surface of an oxide layer formed by an oxide of the valve metal on the surface of a cathode substrate formed by the valve metal and having etching pits, and drying the coating to form a slurry layer; and a pressing stage, applying a pressing treatment to the slurry layer to press the carbon particles into the etching pits and make the carbon particles pierce the oxide layer to form a carbon coating layer having an entry portion entering the etching pits and a penetration portion penetrating the oxide layer and conducting with the cathode substrate.

[0047] As the cathode substrate, a substrate formed of a valve metal and having pits used as a cathode substrate in a conventional solid electrolytic capacitor can be used without particular limitation. For example, a foil formed of valve metals such as aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth and antimony and having a surface area increased by applying a chemical or electrochemical etching treatment can be used, and aluminum foil is particularly preferred. The pits in the cathode substrate can be tunnel pits, sponge pits, through-type pits, or residual core pits, and can be appropriately selected according to the purpose of the solid electrolytic capacitor. These pits can be formed using known AC electrolysis methods and DC electrolysis methods.

[0048] The oxide layer provided on the surface of the cathode substrate can be a natural oxide film that is usually present on the surface of the cathode substrate, or, on this basis, a chemical oxide film can be formed on the surface of the cathode substrate by chemical treatment using a chemical conversion liquid such as an aqueous solution of ammonium borate, an aqueous solution of ammonium adipate, or an aqueous solution of ammonium phosphate, and the chemical oxide film can be used as the oxide layer.

[0049] The carbon slurry used in the coating stage contains at least carbon particles, a binder, and a dispersion medium.

[0050] As carbon particles, carbon particles having various shapes such as fibrous, spherical, and flaky can be used without particular limitation, and examples thereof include porous carbon such as carbon nanotubes, carbon nanofibers, carbon nanohorns, activated carbon, carbon black such as Ketjen black, furnace black, channel black, and acetylene black, amorphous carbon, natural graphite, artificial graphite, graphitized Ketjen black, and mesoporous carbon. These carbon particles can be used alone or as a mixture of two or more. Among them, in the carbon slurry for forming a carbon coating layer having an entry portion into the etch pit, of course, at least carbon particles having a particle size that can enter the etch pit of the cathode substrate are included. In a suitable manner, carbon particles having a particle size that cannot enter the etch pit of the cathode substrate are also included. In this suitable manner, the carbon particles can be formed from the same type of carbon. In other words, the same type of carbon having a wide range of particle size distribution, such as acetylene black having a wide range of particle size distribution, can be used, or a mixture of different types of carbon, such as a mixture of flaky graphite and acetylene black can be used to obtain a wide range of particle size distribution of carbon particles.

[0051] As the binder, known binders such as polytetrafluoroethylene, polyvinylidene fluoride, tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, carboxymethyl cellulose, styrene butadiene rubber can be used alone or in combination of two or more. As the dispersion medium, dispersion mediums that do not adversely affect other constituent elements such as N-methylpyrrolidone, dimethylformamide, tetrahydrofuran, isopropyl alcohol, water, etc. can be used without particular limitation.

[0052] There is no particular limitation on the wet mixing method of carbon particles, binder and dispersion medium for obtaining carbon slurry. It can be performed by manual mixing using a mortar, or by using a known mixing device such as a stirrer or homogenizer. As long as a uniform carbon slurry can be obtained, there is no particular limitation on the mixing time. The carbon particles and binder are generally included in a mass ratio of 80:20 to 95:5.

[0053] The obtained carbon slurry is applied to the surface of the oxide layer provided on the surface of the cathode substrate by a known coating method such as a doctor blade method or a casting method under normal pressure or reduced pressure and dried to form a slurry layer. Then, a pressing step of applying pressure to the obtained slurry layer is performed to form a carbon coating layer.

[0054] Figure 1 The schematic diagram schematically shows an enlarged area near the carbon coating layer 13 in the cross section of the cathode 10 formed using the cathode substrate 11 having a residual core type sponge-like pit. The solid electrolytic capacitor of the present invention is characterized in that the carbon coating layer 13 of the cathode 10 has an entry portion 13a that enters the etched pit 11a and a penetration portion 13b that penetrates the oxide layer 12 and conducts with the cathode substrate 11.

[0055] Before the carbon slurry is applied, a base layer containing a conductive inorganic material such as carbon, titanium nitride, or titanium carbide may be provided on the surface of the oxide layer by using a vapor deposition method such as vacuum vapor deposition or ion plating. The base layer formed by the vapor deposition method may be formed only on the outer surface of the cathode substrate (the surface where no etch pits are formed) on the surface of the oxide layer. Figure 1 Note 11b.) on the surface of the oxide layer, not formed on the surface of the etch pit ( Figure 1 Note 11c.) on the surface of the oxide layer.

[0056] The pressing stage can be performed by roller pressing or vertical pressing. It is necessary to apply pressure in such a way that the carbon particles are pressed into the etched pits of the cathode substrate and the carbon particles pierce the oxide layer. In the case where a base layer is provided on the outer surface of the cathode substrate, it is necessary to apply pressure in such a way that the carbon particles pierce the base layer and the oxide layer. Whether the carbon particles pierce the oxide layer can be simply determined by a preliminary experiment to investigate the correlation between the interface resistance and pressure of the cathode. If the above interface resistance is selected to be 10mΩcm 2 Below, preferably 6 mΩcm 2 Below, more preferably 3mΩcm 2 The pressure during pressing varies depending on the pressing device used, the type of cathode substrate, etc. When applying pressure by roller pressing, 0.5 kNcm is generally used. -1 Above line pressure.

[0057] In addition, if the length of the entry portion of the carbon coating layer ( Figure 1 The average value of Hb is the length of the pit ( Figure 1 If the carbon coating layer is more than 1 / 5 of the average value of Ha), preferably more than 1 / 4, the close adhesion between the carbon coating layer and the collector in contact with the carbon coating layer can be properly ensured, the interface resistance between the carbon coating layer and the collector can be reduced, and the peeling of the carbon coating layer can be properly suppressed, so it is preferred.

[0058] If the carbon coating layer contains particles having a particle size that cannot enter the etch pit as carbon particles, then the particles are substantially present in the region other than the entry portion of the carbon coating layer, and in the pressing stage, the particles play a role in compressing and deforming the etch pit to appropriately improve the adhesion between the carbon coating layer and the collector in contact with the carbon coating layer, and appropriately reduce the interface resistance between the carbon coating layer and the collector, and also play a role in appropriately pressing the carbon particles having a particle size that can enter the etch pit into the etch pit. On the other hand, the carbon particles having a particle size that can enter the etch pit are filled not only into the entry portion of the carbon coating layer, but also into the gaps between the large carbon particles that exist only in the region other than the entry portion, and thus exist in the entire carbon coating layer.

[0059] In addition, if the carbon particles having a particle size that cannot enter the etch pits are formed by flaky graphite, the flaky graphites are easily oriented in a manner that overlaps the basal surfaces of each other, thereby compressing and deforming the etch pits, and are easy to pierce the oxide layer and conduct with the cathode substrate. In addition, if flaky graphite and carbon black are used together, it is easy to press the carbon black into the etch pits and between the flaky graphites to form a carbon coating layer that is particularly dense and has excellent conductivity and excellent adhesion to the collector. As a result, a solid electrolytic capacitor with particularly excellent high-frequency characteristics and high-temperature stability can be obtained. The mass ratio of flaky graphite and carbon black is generally included in the range of 90:10 to 25:75.

[0060] (2) Anode formation process

[0061] In the anode forming process, a dielectric layer is formed by oxidizing the surface of an anode substrate formed of a valve metal. As the anode substrate, a substrate formed of a valve metal used as an anode substrate in a conventional solid electrolytic capacitor can be used without particular limitation. For example, a foil formed of valve metals such as aluminum, tantalum, niobium, titanium, hafnium, zirconium, zinc, tungsten, bismuth and antimony and having a surface area increased by applying a chemical or electrochemical etching treatment can be used, and aluminum foil is particularly preferred. The etch pits in the anode substrate can be tunnel pits, sponge pits, through-type pits, or residual core pits, which can be appropriately selected according to the purpose of the solid electrolytic capacitor. These etch pits can be formed using known alternating current electrolysis methods and direct current electrolysis methods. The dielectric layer on the surface of the anode substrate can be formed using a known method of applying a chemical treatment using a chemical solution such as an aqueous solution of ammonium borate, an aqueous solution of ammonium adipate, or an aqueous solution of ammonium phosphate to the anode substrate.

[0062] (3) Electrolyte formation process

[0063] In the electrolyte forming process, the carbon coating layer of the cathode is made to face the dielectric layer of the anode, and a solid electrolyte layer containing a conductive polymer is formed between them. A spacer is usually arranged between the carbon coating layer of the cathode and the dielectric layer of the anode, and the solid electrolyte layer in contact with both the carbon coating layer of the cathode and the dielectric layer of the anode is maintained by the spacer. For example, the strip-shaped cathode and the anode can be stacked with the spacer so that the carbon coating layer of the cathode faces the dielectric layer of the anode, and then wound, thereby forming a capacitor element, and then forming a solid electrolyte layer. In addition, the cathode and the anode of the desired shape can be stacked with the spacer so that the carbon coating layer of the cathode faces the dielectric layer of the anode, thereby forming a capacitor element, and then forming a solid electrolyte layer. In addition, after forming a capacitor element in which multiple groups of cathodes and anodes are alternately stacked in a manner that sandwiches the spacer and makes the carbon coating layer of the cathode face the dielectric layer of the anode, a solid electrolyte layer is formed. As spacers, woven or non-woven fabrics formed from cellulose fibers, such as Manila paper, kraft paper, Spanish straw pulp paper, hemp paper, cotton paper, rayon and mixed papers thereof, woven or non-woven fabrics formed from polyester resins such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate and their derivatives, polytetrafluoroethylene resins, polyvinylidene fluoride resins, vinylon resins, aliphatic polyamides, semi-aromatic polyamides, wholly aromatic polyamides and other polyamide resins, polyimide resins, polyethylene resins, polypropylene resins, trimethylpentene resins, polyphenylene sulfide resins, acrylic resins, etc., cellophane, mixed papers of cellophane and Manila paper, kraft paper, etc. can be used.

[0064] As the monomer for obtaining the conductive polymer, the monomer having a π-conjugated double bond which has been used in the past for producing the conductive polymer can be used without particular limitation. Representative monomers are shown below. These monomers can be used alone or in the form of a mixture of two or more.

[0065] First, thiophene and thiophene derivatives can be mentioned, for example, 3-alkylthiophenes such as 3-methylthiophene and 3-ethylthiophene, 3,4-dialkylthiophenes such as 3,4-dimethylthiophene and 3,4-diethylthiophene, 3-alkoxythiophenes such as 3-methoxythiophene and 3-ethoxythiophene, 3,4-dialkoxythiophenes such as 3,4-dimethoxythiophene and 3,4-diethoxythiophene, 3,4-methylenedioxythiophene, 3,4-ethylenedioxythiophene, 3,4-(1,2-propylenedioxy)thiophene and the like, Thiophene, 3,4-methyleneoxythiothiophene, 3,4-ethyleneoxythiothiophene, 3,4-(1,2-propyleneoxythio)thiophene and the like 3,4-alkyleneoxythiothiophenes, 3,4-methylenedithiothiophene, 3,4-ethylenedithiothiophene, 3,4-(1,2-propylenedithio)thiophene and the like 3,4-alkylenedithiothiophenes, thieno[3,4-b]thiophene, isopropylthieno[3,4-b]thiophene, tert-butylthieno[3,4-b]thiophene and the like alkylthieno[3,4-b]thiophene.

[0066] In addition, pyrrole and pyrrole derivatives can be mentioned, for example, N-alkylpyrroles such as N-methylpyrrole and N-ethylpyrrole, 3-alkylpyrroles such as 3-methylpyrrole and 3-ethylpyrrole, 3-alkoxypyrroles such as 3-methoxypyrrole and 3-ethoxypyrrole, N-phenylpyrrole, N-naphthylpyrrole, 3,4-dialkylpyrroles such as 3,4-dimethylpyrrole and 3,4-diethylpyrrole, and 3,4-dialkoxypyrroles such as 3,4-dimethoxypyrrole and 3,4-diethoxypyrrole. In addition, aniline and aniline derivatives may be mentioned, for example, 2,5-dialkylanilines such as 2,5-dimethylaniline and 2-methyl-5-ethylaniline, 2,5-dialkoxyanilines such as 2,5-dimethoxyaniline and 2-methoxy-5-ethoxyaniline, 2,3,5-trimethoxyaniline, 2,3,5-trialkoxyanilines such as 2,3,5-triethoxyaniline, 2,3,5,6-tetramethoxyaniline, 2,3,5 , 2,3,5,6-tetraalkoxyanilines such as 6-tetraethoxyaniline, and furan and furan derivatives, for example, 3-alkylfurans such as 3-methylfuran and 3-ethylfuran, 3,4-dialkylfurans such as 3,4-dimethylfuran and 3,4-diethylfuran, 3-alkoxyfurans such as 3-methoxyfuran and 3-ethoxyfuran, and 3,4-dialkoxyfurans such as 3,4-dimethoxyfuran and 3,4-diethoxyfuran.

[0067] As the monomer, it is preferred to use a monomer selected from thiophenes having substituents at positions 3 and 4. The substituents at positions 3 and 4 of the thiophene ring can form a ring together with the carbon atoms at positions 3 and 4. In particular, 3,4-(ethylenedioxythiophene) is preferred because it can provide a conductive polymer having high conductivity and excellent heat resistance.

[0068] The solid electrolyte layer may be formed by electrolytic polymerization or chemical polymerization, or may be formed using a dispersion containing at least conductive polymer particles and a dispersion medium.

[0069] Electropolymerization is carried out by introducing the above capacitor element into a polymerization solution containing at least a monomer, a supporting electrolyte and a solvent and applying a voltage between the anode and the cathode. In the process of electropolymerization, anions released from the supporting electrolyte are contained in the conductive polymer layer as a dopant. As the solvent of the polymerization solution for electropolymerization, a solvent that can dissolve the monomer and supporting electrolyte of the desired amount and does not adversely affect the electropolymerization can be used without particular limitation. As an example, water, methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, butyronitrile, acetone, methyl ethyl ketone, tetrahydrofuran, 1,4-dioxane, γ-butyrolactone, methyl acetate, ethyl acetate, methyl benzoate, ethyl benzoate, ethylene carbonate, propylene carbonate, nitromethane, nitrobenzene, sulfolane, dimethyl sulfolane. These solvents can be used alone or in combination of two or more.

[0070] As the supporting electrolyte contained in the polymer solution for electrolytic polymerization, the compound that releases the dopant contained in the previous conductive polymer can be used without particular limitation. For example, in addition to the inorganic acids such as boric acid, nitric acid, phosphoric acid, acetic acid, oxalic acid, citric acid, etc., sulfonic acids such as methanesulfonic acid, dodecylsulfonic acid, p-toluenesulfonic acid, and their salts can also be exemplified. In addition, polycarboxylic acids such as polyacrylic acid, polymethacrylic acid, polymaleic acid, polysulfonic acids such as polystyrenesulfonic acid, polyvinylsulfonic acid, and their salts can also be used as supporting electrolytes. In addition, boron complexes such as boron disalicylic acid, boron dioxalic acid, boron dimalonic acid, sulfonyl imide and their salts can also be used as supporting electrolytes. As salts, alkali metal salts such as lithium salts, sodium salts, potassium salts, ammonium salts, ethylammonium salts, alkylammonium salts such as butylammonium salts can be exemplified. These supporting electrolytes may be used alone or in combination of two or more. Depending on the type of the supporting electrolyte, the supporting electrolyte is used in an amount not exceeding the saturated solubility in the polymerization solution and at a concentration sufficient to obtain a current for electrolytic polymerization.

[0071] Electrolytic polymerization can be carried out by any method of constant potential method, constant current method and potential scanning method. In the case of constant potential method, although it depends on the type of monomer, the potential is preferably 1.0 to 1.5 V for saturated calomel electrode, and in the case of constant current method, although it depends on the type of monomer, it is preferably 1 to 10000 μA / cm 2The current value of the potential scanning method depends on the type of monomer, but it is suitable to scan the range of 0 to 1.5 V at a rate of 5 to 200 mV / sec for a saturated calomel electrode. The polymerization temperature is not strictly limited, but is generally in the range of 10 to 60°C. The polymerization time is also not strictly limited, but is generally in the range of 1 minute to 10 hours.

[0072] The formation of the solid electrolyte layer by chemical polymerization can be carried out by the following method, that is, a solution in which both the monomer and the oxidant are dissolved in a solvent is prepared, and the solution is impregnated between the carbon coating layer of the cathode and the dielectric layer of the anode, and then dried; or a solution in which the monomer is dissolved in a solvent and a solution in which the oxidant is dissolved in a solvent are prepared, and these solutions are alternately impregnated between the carbon coating layer of the cathode and the dielectric layer of the anode, and then dried. As the solvent, for example, water, methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, butyronitrile, acetone, methyl ethyl ketone, tetrahydrofuran, 1,4-dioxane, γ-butyrolactone, methyl acetate, ethyl acetate, methyl benzoate, ethyl benzoate, ethylene carbonate, propylene carbonate, nitromethane, nitrobenzene, sulfolane, dimethylsulfolane. These solvents can be used alone or in combination of two or more.

[0073] As the oxidant, trivalent iron salts such as iron (III) p-toluenesulfonate, iron (III) naphthalenesulfonate, and iron (III) anthraquinonesulfonate, or persulfates such as ammonium peroxodisulfate and sodium peroxodisulfate can be used. A single compound or two or more compounds can be used. The polymerization temperature is not strictly limited, but is generally in the range of 10 to 60° C. The polymerization time is also not strictly limited, but is generally in the range of 1 minute to 10 hours.

[0074] In addition, after the dispersion liquid containing at least the particles of the conductive polymer and the dispersion medium is impregnated between the carbon coating layer of the above-mentioned cathode and the dielectric layer of the above-mentioned anode, it is dried, thereby also a solid electrolyte layer can be formed. As the dispersion medium in the above-mentioned dispersion liquid, for example, water, methanol, ethanol, isopropanol, butanol, ethylene glycol, acetonitrile, butyronitrile, acetone, methyl ethyl ketone, tetrahydrofuran, 1,4-dioxane, γ-butyrolactone, methyl acetate, ethyl acetate, methyl benzoate, ethyl benzoate, ethylene carbonate, propylene carbonate, nitromethane, nitrobenzene, cyclopentane, dimethyl cyclopentane can be used, but preferably water is used as the dispersion medium.

[0075] The above-mentioned dispersion can be obtained, for example, by adding monomers, an acid or a salt thereof that releases dopants, and an oxidant to water, stirring until chemical oxidation polymerization is completed, then removing the oxidant and residual monomers by purification methods such as ultrafiltration, cation exchange, and anion exchange, and then subjecting to dispersion treatments such as ultrasonic dispersion treatment, high-speed fluid dispersion treatment, and high-pressure dispersion treatment as required. In addition, it can be obtained by adding monomers, an acid or a salt thereof that releases dopants to water, stirring while performing electrolytic oxidation polymerization, then removing residual monomers by purification methods such as ultrafiltration, cation exchange, and anion exchange, and then subjecting to dispersion treatments such as ultrasonic dispersion treatment, high-speed fluid dispersion treatment, and high-pressure dispersion treatment as required. In addition, it can be obtained by filtering the liquid obtained by the above-mentioned chemical oxidation polymerization method or electrolytic polymerization method to separate the coagulant, adding it to water after sufficient washing, and subjecting it to dispersion treatments such as ultrasonic dispersion treatment, high-speed fluid dispersion treatment, and high-pressure dispersion treatment. The content of the conductive polymer particles in the dispersion is generally in the range of 1.0 to 3.0 mass %, preferably in the range of 1.5 to 2.0 mass %. The drying temperature is not strictly limited, but is generally in the range of 50 to 200° C. The drying time is also not strictly limited, but is generally in the range of 1 to 10 hours.

[0076] After the electrolyte formation process is completed, the capacitor element with the added solid electrolyte layer is placed in an outer packaging box and sealed to obtain the solid electrolytic capacitor of the present invention. It should be noted that as a sealing method for a capacitor element with a solid electrolyte layer, a method of molding the capacitor element with a resin can be selected. In the solid electrolytic capacitor of the present invention, the above-mentioned carbon coating layer with a special shape can be used to achieve high electrostatic capacitance, low ESR, excellent high-frequency characteristics and high high-temperature durability.

[0077] It should be noted that in the solid electrolytic capacitor of the present invention, the electrolyte can also be impregnated into the solid electrolyte layer to form a hybrid electrolytic capacitor. The electrolyte increases the electrostatic capacitance of the capacitor and reduces the ESR. In addition, the repair performance of the dielectric oxide film is improved by the electrolyte, and the life of the capacitor is extended. In order to make a hybrid electrolytic capacitor, an electrolyte suitable for low voltage or medium and high voltage can be used without special restrictions. As an example, an electrolyte obtained by dissolving electrolytes such as ammonium salts, quaternary ammonium salts, quaternary amidinium salts, and amine salts of boron disalicylic acid, boron dioxalic acid, boron diglycolic acid, 1,6-decanedioic acid, azelaic acid, adipic acid, phosphoric acid, boric acid, etc. in solvents such as γ-butyrolactone, ethylene glycol, polyoxyethylene glycol, cyclopentane sulfone, polycarbonate, and mixtures thereof at a specified concentration can be cited.

[0078] Example

[0079] The present invention will be described below using the following examples; however, the present invention is not limited to the following examples.

[0080] Example 1

[0081] Aluminum foil with sponge-like pits formed at an etching rate (ratio of actual surface area to projected area) of 22 was used as a cathode substrate for obtaining a cathode. The aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and a chemical conversion voltage of 1.2 V was formed on the surface of the aluminum foil. fs The formed oxide film (oxide layer).

[0082] Flake graphite with an average particle size of 4 μm and carbon black with an average primary particle diameter of 50 nm and an average secondary particle diameter of 0.3 μm were used as carbon particles. They were mixed in a mass ratio of 75:25, and the resulting mixture, styrene butadiene rubber, and an aqueous solution of sodium carboxymethyl cellulose were mixed in a mass ratio of 84:10:6 and dispersed using a stirrer to prepare a carbon slurry.

[0083] The obtained carbon slurry was applied onto the above-mentioned chemical oxide film and dried to form a slurry layer. The slurry layer was subjected to a linear pressure of 5.38 kNcm -1 After the carbon coating layer with a thickness of 1 μm was formed by applying a pressing process by roller pressing, the projected area was 2.1 cm 2 Punching is performed to obtain a cathode for a solid electrolytic capacitor. The cathode cross-section was observed using an SEM photograph, and as a result, the carbon black penetrated to a position of about 1 / 3 of the length of the etch pit. In addition, in the area of ​​the carbon coating layer other than the penetration portion, the flaky graphite is oriented so that the basal surfaces overlap with each other, and the graphite is filled with carbon black. Subsequently, the above-mentioned carbon slurry is applied to the carbon coating layer of the cathode for the solid electrolytic capacitor and dried to prepare a confirmation cathode having a carbon coating layer with a thickness of 20 μm. The interface resistance of the cathode is measured using an electrode resistance measurement system (manufactured by Hioki Electric Chemical Co., Ltd., model RM2610), and the result is 1.63 mΩcm 2 , and the value is used to judge whether the carbon coating layer of the cathode for the solid electrolytic capacitor is conductive with the aluminum of the cathode substrate.

[0084] An aluminum foil with sponge-like pits was used as an anode substrate for obtaining an anode. The aluminum foil was subjected to a chemical conversion treatment using an aqueous ammonium adipate solution to form a chemical conversion voltage of 45.6 V on the surface of the aluminum foil. fs Then, the aluminum foil with the additional dielectric layer was placed on a projected area of ​​2.1 cm 2 The punching was performed with ammonium dihydrogen phosphate aqueous solution as the forming solution at a current density of 0.2 mA cm -2The anode for a solid electrolytic capacitor was obtained by applying a chemical conversion treatment for 10 minutes under the conditions of , thereby repairing the end surface portion formed during punching.

[0085] Aluminum terminals were ultrasonically welded to the obtained anode and cathode, and the dielectric layer of the anode and the carbon coating layer of the cathode were faced to each other via a separator folded 99 times, and fixed with an imide tape to obtain a capacitor element.

[0086] The particles of poly(3,4-ethylenedioxythiophene) and polystyrene sulfonic acid were dispersed in a dispersion medium obtained by adding 5% by mass of ethylene glycol to water to obtain a dispersion liquid for forming a solid electrolyte layer. The obtained dispersion liquid was impregnated into the above capacitor element under a pressure of 30 kPa for 120 seconds and dried at 110°C for 120 minutes. Then, the capacitor element with the added solid electrolyte layer was sealed with a laminate to obtain a solid electrolytic capacitor with a rated voltage of 25WV.

[0087] The obtained fixed electrolytic capacitor was aged for 60 minutes at 105°C by applying a voltage of 28.8V. As the initial characteristics of the capacitor, the electrostatic capacitance at 120Hz and 10kHz and the ESR at 10kHz and 100kHz were measured at 20°C. Then, as a durability test, 500 cycles of charge and discharge were repeated at a high temperature of 105°C. As the characteristics after the durability test, the electrostatic capacitance at 120Hz and 10kHz and the ESR at 10kHz and 100kHz were measured again at 20°C. It should be noted that the charging and discharging was carried out between 25V and 0V, with a charging current of 20mA for 10 seconds and a discharge resistance of 0Ω (no resistance) for 10 seconds.

[0088] Comparative Example 1

[0089] The steps of Example 1 were repeated except that the slurry layer was not pressed during the cathode formation process. The thickness of the carbon coating layer of the cathode for the solid electrolytic capacitor was 1 μm. In addition, the cathode cross section was confirmed using an SEM photograph, and as a result, basically no carbon particles were observed in the etch pits. In addition, the interface resistance of the cathode for confirmation, which had a carbon coating layer with a thickness of 20 μm obtained by coating the above-mentioned carbon slurry on the carbon coating layer of the cathode for the solid electrolytic capacitor and drying it, was 31.2 mΩcm 2 , it was determined that the carbon coating layer of the cathode for the solid electrolytic capacitor was not conductive with the aluminum of the cathode substrate.

[0090] Example 2

[0091] The steps of Example 1 were repeated except that only carbon black having an average primary particle diameter of 35 nm and an average secondary particle diameter of 0.3 μm was used as carbon particles to prepare a carbon slurry for forming a carbon coating layer of a cathode. The thickness of the carbon coating layer of the cathode for a solid electrolytic capacitor was 1 μm. In addition, the cathode cross-section was confirmed using an SEM photograph, and as a result, the carbon black entered to a position of about 1 / 3 of the length of the etch pit. In addition, the interface resistance of the cathode for confirmation, which had a carbon coating layer with a thickness of 20 μm obtained by applying the above-mentioned carbon slurry on the carbon coating layer of the cathode for the above-mentioned solid electrolytic capacitor and drying it, was 1.83 mΩcm 2 , judging whether the carbon coating layer of the cathode for the solid electrolytic capacitor is conductive with the aluminum of the cathode substrate.

[0092] Comparative Example 2

[0093] The steps of Example 2 were repeated except that the slurry layer was not pressed during the cathode formation process. The thickness of the carbon coating layer of the cathode for the solid electrolytic capacitor was 1 μm. In addition, the cathode cross section was confirmed using an SEM photograph, and as a result, the entry of carbon particles was observed only near the opening of the etch pit. In addition, the interface resistance of the cathode for confirmation, which had a carbon coating layer with a thickness of 20 μm obtained by coating the above-mentioned carbon slurry on the carbon coating layer of the cathode for the solid electrolytic capacitor and drying it, was 19.7 mΩcm 2 , it was determined that the carbon coating layer of the cathode for the solid electrolytic capacitor was not conductive with the aluminum of the cathode substrate.

[0094] Comparative Example 3

[0095] Aluminum foil with sponge-like pits formed at an etching rate of 70 was used as a cathode substrate for obtaining a cathode. The aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and a chemical conversion voltage of 3 V was formed on the surface of the aluminum foil. fs After the oxide film (oxide layer) is formed, the projected area is 2.1cm 2 The cathode for the solid electrolytic capacitor was punched out. In this comparative example, the coating layer on the chemically formed oxide film was not formed. A solid electrolytic capacitor was prepared using the cathode, the anode used in Example 1, and the dispersion, and the characteristics of the obtained solid electrolytic capacitor were evaluated under the same conditions as those shown in Example 1.

[0096] Comparative Example 4

[0097] Aluminum foil with sponge-like pits formed at an etching rate of 7 or less was used as a cathode substrate for obtaining a cathode. The aluminum foil was subjected to a chemical conversion treatment using an aqueous solution of ammonium dihydrogen phosphate as a chemical conversion solution, and a chemical conversion voltage of 5 V was formed on the surface of the aluminum foil. fsThen, instead of the carbon coating layer, a vapor-deposited film containing titanium carbide was formed on the surface of the chemically formed oxide film by arc ion plating, with a projected area of ​​2.1 cm 2 The cathode for solid electrolytic capacitor was obtained by punching. The titanium carbide vapor-deposited film did not enter the etch pit. A solid electrolytic capacitor was prepared using the cathode, the anode used in Example 1, and the dispersion, and the characteristics of the obtained solid electrolytic capacitor were evaluated under the same conditions as those shown in Example 1.

[0098] Comparative Example 5

[0099] Aluminum foil without etch pits was used as the cathode substrate for obtaining the cathode. In this example, a natural oxide film was used as the oxide layer instead of a chemically formed oxide film. Then, a carbon-containing vapor-deposited film was formed on the surface of the natural oxide film by sputtering instead of the carbon coating layer, and a projection area of ​​2.1 cm was obtained. 2 The cathode was punched out to obtain a cathode for a solid electrolytic capacitor. A solid electrolytic capacitor was prepared using the cathode, the anode used in Example 1, and the dispersion. The characteristics of the obtained solid electrolytic capacitor were evaluated under the same conditions as those shown in Example 1.

[0100] Table 1 shows the capacitance values ​​at 20° C. obtained for the solid electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 to 5, and Table 2 shows the ESR values ​​at 20° C. obtained for the solid electrolytic capacitors of Examples 1 and 2 and Comparative Examples 1 to 5. In the tables, carbon black is represented by CB.

[0101]

[0102]

[0103] The titanium carbide vapor-deposited film in the cathode of the capacitor of Comparative Example 4, the carbon vapor-deposited film in the cathode of the capacitor of Comparative Example 5, and the carbon coating layer formed by coating the carbon slurry but not pressing in the cathode of the capacitor of Comparative Examples 1 and 2 have long been known as a coating layer that increases the capacitance of the capacitor by making the cathode capacitance close to infinity and inhibits the growth of the aluminum oxide film in the cathode (see Patent Documents 2 to 4). Comparing the electrostatic capacitance and ESR of the capacitors of Comparative Examples 1 and 2 with the electrostatic capacitance and ESR of the capacitor of Comparative Example 3 having a cathode without a coating layer, it can be seen that although the changes in electrostatic capacitance and ESR before and after the charge and discharge test are indeed reduced and the electrostatic capacitance at 120Hz is increased, the electrostatic capacitance at 10kHz is reduced, and there is a problem in high-frequency characteristics. In contrast, although the capacitors of Comparative Examples 1 and 2 show lower ESR than the capacitors of Comparative Examples 4 and 5, the electrostatic capacitance at 10kHz is still low, and there is a problem in high-frequency characteristics.

[0104] In contrast, in the capacitors of Examples 1 and 2 having a cathode having a carbon coating layer formed by coating a carbon slurry and pressed, the ESR of the capacitor of Example 1 is compared with the value of the corresponding capacitor of Comparative Example 1, and the ESR of the capacitor of Example 2 is compared with the value of the corresponding capacitor of Comparative Example 2. It can be clearly understood that the ESR value is significantly reduced regardless of the condition of 10 kHz or the condition of 100 kHz, and the change of ESR before and after the charge and discharge test is roughly the same and excellent. The significant reduction in the ESR of the capacitors of Examples 1 and 2 is believed to be due to the improvement of the adhesion between the carbon coating layer and the collector contacting the carbon coating layer, which reduces the interface resistance between them. In addition, by comparing the electrostatic capacitance of the capacitor of Example 1 with the corresponding value of the capacitor of Comparative Example 1, and comparing the electrostatic capacitance of the capacitor of Example 2 with the corresponding value of the capacitor of Comparative Example 2, it can be clearly understood that the electrostatic capacitance of the capacitors of Examples 1 and 2 increases both under the condition of 120 Hz and under the condition of 10 kHz. In addition, the change in electrostatic capacitance at 10 kHz before and after the charge and discharge test is also improved, and the high-frequency characteristics are improved.

[0105] The method of increasing the capacitance of the capacitor by making the cathode capacitance close to infinity by using the coating layer has been given in patent documents 1 to 4. The previous measurements were mainly carried out under the condition of 120Hz, and the electrostatic capacitance in the high-frequency region (10kHz) was not given. In addition, it can be understood from the electrostatic capacitance of the capacitors of comparative examples 1 to 5 that the electrostatic capacitance in the high-frequency region (10kHz) will not increase by using the countermeasures of these existing documents.

[0106] The electrostatic capacitance in the high frequency region (10kHz) is considered to be determined by the relationship between the interface resistance of the components formed by the cathode and the solid electrolyte layer (the interface resistance measured between the solid electrolyte layer and the cathode substrate, which depends on all interfaces contained in the above-mentioned components) and the resistance of the oxide film (oxide layer) of the collector. It can be considered that in the capacitors of Comparative Examples 1 and 2 where the pressing treatment is not performed to form the carbon coating layer, since the interface resistance between the collector and the carbon coating layer is large, the former is larger than the latter, and as a result, the influence of the cathode capacitance generated by the oxide film of the collector is revealed, and the capacitor capacitance becomes lower. In the capacitors of Examples 1 and 2 where the pressing treatment is performed to form the carbon coating layer, since the interface resistance between the collector and the carbon coating layer becomes smaller, the former is smaller than the latter, and as a result, the influence of the cathode capacitance caused by the oxide film of the collector is not revealed, and the capacitor capacitance becomes higher.

[0107] Comparing the characteristics of the capacitor of Example 1 with those of the capacitor of Example 2, it can be seen that the ESR of the capacitor of Example 1 is particularly low, the electrostatic capacitance of the capacitor of Example 1 at 10kHz is particularly high, and the change in electrostatic capacitance before and after the charge and discharge test is particularly small, and the capacitor of Example 1 is particularly excellent in high-frequency characteristics and high-temperature stability. This is considered to be because the flaky graphite that essentially only exists in the area of ​​the carbon coating except the entry portion is easy to be oriented in a manner that overlaps each other's basal surfaces and compresses the etch pits, and it is easy to pierce the oxide layer and conduct with the cathode substrate. In addition, it is easy to press carbon black into the etch pits and between the flaky graphite, forming a dense and excellently conductive carbon coating layer with excellent adhesion to the collector.

[0108] Industrial Applicability

[0109] According to the present invention, a solid electrolytic capacitor having high electrostatic capacitance, low ESR, excellent high-frequency characteristics, and high high-temperature durability can be obtained.

Claims

1. A solid electrolytic capacitor, characterized in that: have: A cathode having a cathode substrate, an oxide layer and a carbon coating layer, wherein the cathode substrate is formed of a valve metal and has an etch pit, the oxide layer is provided on the surface of the cathode substrate and is formed of an oxide of the valve metal, and the carbon coating layer is provided on the surface of the oxide layer and contains carbon particles, and has an entry portion that enters the etch pit and a penetration portion that penetrates the oxide layer and is in electrical communication with the cathode substrate; An anode having an anode substrate formed of a valve metal and a dielectric layer formed of an oxide of the valve metal constituting the anode substrate and provided on a surface of the anode substrate; as well as a solid electrolyte layer provided between the carbon coating layer of the cathode and the dielectric layer of the anode, comprising a conductive polymer, The average value of the length of the penetration portion of the carbon coating layer is 1 / 5 or more of the average value of the length of the etch pits.

2. The solid electrolytic capacitor according to claim 1, wherein: The carbon coating layer includes carbon particles having a particle size that cannot enter the etching pits.

3. The solid electrolytic capacitor according to claim 1 or 2, wherein: The carbon particles in the carbon coating layer are formed of the same type of carbon.

4. The solid electrolytic capacitor according to claim 2, wherein: The carbon particles in the carbon coating layer having a particle size that does not enter the etching pits are formed of flaky graphite.

5. The solid electrolytic capacitor according to claim 1 or 2, wherein: The average value of the length of the penetration portion of the carbon coating layer is 1 / 4 or more of the average value of the length of the etch pits.

6. The solid electrolytic capacitor according to claim 1 or 2, wherein: The interfacial resistance of the cathode is 10 mΩcm 2 the following.

7. A method for manufacturing a solid electrolytic capacitor, characterized in that: include: A cathode forming step, comprising: a coating stage, coating a carbon slurry containing carbon particles on a surface of an oxide layer formed of an oxide of a valve metal provided on a surface of a cathode substrate formed of a valve metal and having an etch pit, and drying the coating to form a slurry layer; and a pressing stage, applying a pressing treatment to the slurry layer, thereby pressing the carbon particles into the etch pit and causing the carbon particles to pierce the oxide layer, thereby forming a carbon coating layer having an entry portion that enters the etch pit and a penetration portion that penetrates the oxide layer and is in conduction with the cathode substrate, wherein the average length of the entry portion of the carbon coating layer is at least 1 / 5 of the average length of the etch pit; an anode forming step of forming a dielectric layer by oxidizing a surface of an anode substrate formed of a valve metal; and The electrolyte forming step forms a solid electrolyte layer including a conductive polymer between the carbon coating layer of the cathode and the dielectric layer of the anode.

8. The method for manufacturing a solid electrolytic capacitor according to claim 7, wherein: The carbon slurry contains carbon particles having a particle size that cannot enter the etch pits.

Citation Information

Patent Citations

  • Solid electrolytic capacitor and its manufacture

    JP2000114109A

  • Solid electrolytic capacitor

    JP2005109272A

  • Electrolyte capacitor and manufacturing method thereof

    JP2006190878A

  • Aluminum cathode foil for electrolytic capacitor and manufacturing method thereof

    JP2007095865A